2023
DOI: 10.1590/1980-220x-reeusp-2022-0329en
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and experience of Primary Education teachers regarding childhood asthma: mixed study

Abstract: Objective: To analyze the knowledge of Primary Education teachers regarding asthma and learn about their experiences with the exacerbation of symptoms at school. Method: Sequential explanatory mixed study. In the quantitative stage, the Newcastle Asthma Knowledge Questionnaire and the characterization instrument were applied. Data analyzed by descriptive and inferential statistics. The production of qualitative data occurred from written statements analyzed using the deductive content analysis method. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…[ 26 ] In Saudi Arabia, Al-Qurain and Alslman found that more than half of their sample in Saudi Arabia had no knowledge of providing first aid for asthma,[ 24 ] a finding similar to that ofBrosso et al . [ 27 ] in Brazil.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 26 ] In Saudi Arabia, Al-Qurain and Alslman found that more than half of their sample in Saudi Arabia had no knowledge of providing first aid for asthma,[ 24 ] a finding similar to that ofBrosso et al . [ 27 ] in Brazil.…”
Section: Literature Reviewmentioning
confidence: 99%